Possibilities of speech analysis for early stress recognition in office environment - Al-Qadasi, E. (ХНУРЕ, 2023)
This work is devoted to speech analysis for early stress recognition in office environment and outlines a study on the use of speech analysis for early detection of stress. It was studied what parameters of speech are changed under stress situations. It has been found out that under stress situations, changes in pitch (fundamental frequency) and in the speaking rate are usual, together with variations in features related to the energy and spectral characteristics of the glottal pulse. Speech analysis can be an effective tool for detecting stress in office environment, which could help to prevent negative outcomes and improve employee well-being and productivity.
Keywords: Office worker, pitch, speaking rate, speech analysis, stress.